Oncolytic viruses - Engeland, Christine Elisabeth (Humana, 2020)
Introduction to Oncolytic Virotherapy -- Methods for Modification of Therapeutic Viruses -- Tumor Targeting of Oncolytic Adenoviruses using Bispecific Adapter Proteins -- Development of Entry-targeted Oncolytic Measles Viruses -- Insert Stability and In Vivo Testing of MicroRNA-Detargeted Oncolytic Picornaviruses -- Ex vivo Virotherapy with Myxoma Virus to Treat Cancer -- Immunomodulation in Oncolytic Measles Virotherapy -- A Functional Assay to Determine the Capacity of Oncolytic Viruses to Induce Immunogenic Tumor Cell Death -- Design and Production of Newcastle Disease Virus for Intratumoral Immunomodulation -- Analysis of Immunological Treatment Effects of Virotherapy in Tumor Tissue -- Immunohistochemistry for Tumor-infiltrating Immune Cells after Oncolytic Virotherapy -- Detection of Tumor Antigen-specific T-cell Responses after Oncolytic Vaccination -- Evaluation of Oncolytic Virus Induced Therapeutic Tumor Vaccination Effects in Murine Tumor Models -- Delivery of Oncolytic Reovirus by Cell Carriers -- In Vivo Bioimaging for Monitoring Intratumoral Virus Activity -- Oncolytic Immunotherapy for Bladder Cancer Using Coxsackie A21 virus: Using a Bladder Tumour Precision-cut Slice Model System to Assess Viral Efficacy -- Use of Liquid Patient Ascites Fluids as a Pre-clinical Model for Oncolytic Virus Activity -- Generating Primary Models of Human Cancer to Aid in the Development of Clinically-relevant Oncolytic Viruses -- Considerations for Clinical Translation of MG1 Maraba Virus -- Fluorescence in Situ Hybridization (FISH) Detection of Viral Nucleic Acids in Oncolytic H-1 Parvovirus-treated Human Brain Tumors -- Mathematical Modeling of Oncolytic Virotherapy